Mediating Role of Policy Support in the Relationship Between Green Financing and Sustainable Housing Development in Nigeria: A PLS Modeling Approach - Babayo, Musa Mustapha; Milala, Sani Inusa (TECHNOVATE: Journal of Information Technology and Strategic Innovation Management, 2024)
This study examines the impact of Green Financing on Sustainable Housing Development, focusing on the mediating role of Policy Support. As urbanization accelerates, particularly in developing countries, the need for sustainable housing solutions intensifies. Green Financing, which funds environmentally friendly projects, is considered a potential driver of sustainable housing, though its success depends on supportive policies. Using a quantitative approach and structural equation modeling (SEM), the study analyzes data from 500 stakeholders in the housing sector, including policymakers, financial institutions, and developers. Results show that Green Financing significantly boosts Policy Support (path coefficient = 0.832, t-statistic = 31.150, p-value = 0.000), and also has a positive effect on Sustainable Housing Development (path coefficient = 0.636, t-statistic = 9.114, p-value = 0.000). Furthermore, Policy Support plays a significant mediating role in enhancing Sustainable Housing Development (path coefficient = 0.250, t-statistic = 3.458, p-value = 0.001). These findings highlight the importance of integrating Green Financing with strong policy frameworks to promote sustainable housing. The study recommends targeted financial and regulatory measures to encourage green finance, and suggests further research on its long-term impacts.